2015
DOI: 10.1007/s10561-015-9520-y
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic membranes in ophthalmology: long term data on transplantation outcomes

Abstract: The use of amniotic membrane (AM) is a widespread clinical practice for eye surgeries and the treatment of an increasing number of ocular surface pathologies. Here we describe the AM collection methods and donor selection criteria adopted by our tissue bank to distribute 5349 amniotic membrane patches over the last 12 years for the treatment of several ocular pathologies. Specific quality control measures are described and the long term results attained using the reported procedure are presented. A case of AM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 27 publications
0
51
0
1
Order By: Relevance
“…Requests have been received and completed from 58 ophthalmic surgeons across all states and territories except Northern Territory suggesting a basic national demand for AM. Fifty‐nine percent of recipients were male with a mean age of 64.0 ± 17.3 years (range 6 to 93) corresponding with population findings from the existing ophthalmic literature . Seven patients required multiple tissue applications for surface reconstruction or tectonic repair (neoplasia, corneal ulcer at risk of perforation, infectious scleritis and alkali burn).…”
Section: Literature Comparison: Main Indications For Use Of Amnion Timentioning
confidence: 84%
See 1 more Smart Citation
“…Requests have been received and completed from 58 ophthalmic surgeons across all states and territories except Northern Territory suggesting a basic national demand for AM. Fifty‐nine percent of recipients were male with a mean age of 64.0 ± 17.3 years (range 6 to 93) corresponding with population findings from the existing ophthalmic literature . Seven patients required multiple tissue applications for surface reconstruction or tectonic repair (neoplasia, corneal ulcer at risk of perforation, infectious scleritis and alkali burn).…”
Section: Literature Comparison: Main Indications For Use Of Amnion Timentioning
confidence: 84%
“…The leading indication in Mexico and Italian populations is pterygium and corneal ulcer repair, respectively. The incidence of ocular surface neoplasia has been shown to be significantly greater in the southern hemisphere which may have contributed to the increased representation in the local population by comparison . Our sample remains small however and the increased awareness and use of the AM tissue utility is likely to see the list evolve further.…”
Section: Literature Comparison: Main Indications For Use Of Amnion Timentioning
confidence: 92%
“…The reduction in the proliferation of HPDLFs can also be due to foetal hyaluronic acid, which is one of the components of HAM. Foetal hyaluronic acid suppresses the transforming growth factor-beta (TGF-β) signalling by reducing the expression of TGF β-1, β-2 and β-3 isoforms and the expression of the TGF receptor, which has an inhibiting effect on the proliferation of fibroblasts (Lee et al 2000;Paolin et al 2016). This is also the main mechanism behind its anti-scarring properties (Tseng et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, tissue remodeling was reported with their use via stimulating apoptosis of T lymphocytes and regulating activated macrophages. Paolini et al, (2016) also revealed that AM acts as a scaffold for proliferation and differentiation due to its content of fibronectin, elastin, hyaluronic acid and collagen type I, III, IV, V and VI [41] . Also, various growth factors have been detected in cryopreserved AMs including epidermal growth factor and transforming growth factors which play a crucial role in the anti-scarring and anti-inflammatory effects of AM, in addition to enhancing re-epithelialization and healing [42] .…”
Section: Discussionmentioning
confidence: 99%